Polyphase coded radar for target characterization in the open range environment. (1st January 2021) - Sur, Samarendra Nath; Bera, Soumyasree; Singh, Arun Kumar; Shome, Subhankar; Bera, Rabindranath; Maji, Bansibadan
Highlights: Description of the polyphase coded radar system with the link budget analysis. Presents aspect angle pattern of the standard target in open range condition. All experimental results are compared with the theoretically simulated results. We analyze the detectability and environmental effect rejection capabilities. Abstract: This paper has described the development of the spread spectrum radar system and radar cross-section (RCS) measurements in the frequency range of 1–3 GHz, using a LabVIEW controlled fully digital radar setup. In this paper, the performance of a polyphase coded spread spectrum radar is illustrated and compared with the theoretical calculation for bistatic RCS measurements. For the performance calibration, different (sizes) flat plates are used as reference targets and tested over a wide frequency range. Here in addition to the controlling LabView platform is used for radar signal processing. MATLAB platform is used to compute the theoretical RCS pattern for radar performance validation.